Urine calcium and deoxypyridinoline in assessment of response to local radiation therapy for metastatic bone disease - Topkan, E.; Karaoglu, A. (Biomed Central Ltd, 2007)
To evaluate the predictability of urine calcium (Ca2+) and deoxypyridinoline (DPD) in the assessment of response to palliative radiation therapy (RT) for metastatic bone disease. Forty-two patients with osteolytic bone metastases from breast or lung primaries were enrolled in this study. Serial urine Ca2+ and DPD measurements were performed before RT, six weeks, and twelve weeks afterwards. All eligible patients received a total of 30 Gy RT in 3 Gy daily fractions. Pre-irradiation mean urine Ca+2 and DPD levels were 16 +/- 3.7 g/mu mol/dL, and 89.2 +/- 61 pmol/mu mol crea. Both were significantly higher than normal range. A significant correlation between pre-irradiation Ca+2 (r=0.6, p<0.001), DPD (r=0.8, p<0.001) levels and the extent of bone metastases were detected. Thirty-six patients (Group I) were alive without disease progression outside the radiation portal. Urine Ca2+ and DPD levels demonstrated a significant and progressive decrease following RT in Group I patients (p<0.001). Clinical and radiological evaluation revealed occurrence of new bone metastases in six patients (Group II), with concurrent significant increase in concentrations of urine DPD and Ca+2 (p=0.006 for Ca+2 and p=0.009 for DPD, respectively). Urine Ca+2 and DPD levels can be used for assessment of response of bone to local irradiation, and are able to predict further progression of bone metastases in cancer patients.
Keywords: urine calcium; deoxypyridinoline; palliative radiotherapy